New challenges of modernity for Ukrainian tourist industry (compliance program within the framework of logistics management in the conditions of crisis) - Garmash, Sergii; Pererva, P. G. (My University, 2020)
It should be noted that the global financial crisis of 2008, which affected all spheres of people’s livelihoods, pushed the development of the tourist industry. Governments in many countries have begun to pay more attention to this market segment, as it is this segment that is able to restore its position and profit in a relatively short time. Another situation is with the COVID-19 pandemic. When “deferred opportunities” turn into “lost opportunities”. The aim of the research is summarizing the experience of travel companies in overcoming the negative consequences of crisis situations; tracking the typical trends of the behavior of travel companies in the market for the provision of travel services in such situations and development of practical recommendations for the possible use of a compliance program at a travel company as a part of logistics management. Methodology: while working at the article, the following methods of scientific knowledge were used: the method of unity of analysis and synthesis, method of expert assessments, comparative analysis and systemic approach. Scientific novelty: the implementation of a compliance program at a travel company organically fits into the logistics management system. Practical value: the effects of the global economic crisis due to COVID-19 pandemic and the quarantine have yet to be understood. Many domestic travel companies, referring to force majeure, impose penalties on their customers. In order to prevent corruption in such crisis conditions, it is necessary to introduce compliance programs within the travel industry in the framework of logistics management. This will help to meet the needs of the client as well as the development of the travel company even in times of crisis.

Слід зазначити, що світова фінансова криза 2008 року, яка торкнулася усіх сфер життєдіяльності людей, підштовхнула розвиток туристичної галузі. Уряди багатьох країн почали приділяти більше уваги цьому сегменту ринку, оскільки саме цей сегмент здатний за відносно короткий час відновити свої позиції та приносити прибуток. Інша ситуація склалася з пандемією COVID-19, коли «відкладені можливості» перетворюються на «втрачені можливості». Ціллю цього дослідження є узагальнення досвіду туристичних фірм у подоланні негативних наслідків у кризових ситуаціях; простежування тенденцій у поведінці туроператорів на ринку надання туристичних послуг у таких ситуаціях та розробка практичних рекомендацій можливого використання комплаєнс-програми на туристичному підприємстві у рамках логістичного менеджменту для запобігання корупції і несумлінного відношення до клієнтів у кризовій ситуації. Методологія: під час роботи над статтею було використано наступні методи наукового пізнання: метод єдності аналізу та синтезу, метод експертних оцінок, порівняльний аналіз та системний підхід. Наукова новизна: впровадження комплаєнс-програми на туристичному підприємстві органічно вписується у систему логістичного менеджменту. Практичне значення: наслідки економічної світової кризи внаслідок пандемії COVID-19 та карантину ще слід буде осягти. Багато вітчизняних туристичних компаній, посилаючись на форс-мажор, вводять штрафні санкції для своїх клієнтів. Для запобігання корупції в таких кризових умовах на підприємствах туристичної індустрії слід запровадити комплаєнс-програми у рамках логістичного менеджменту. Це сприятиме як задоволенню потреб самого клієнта, так і розвитку діяльності туристичної компанії навіть у кризові часи.
Нові виклики сучасності для української індустрії туризму (комплаєнс-програма в рамках логістичного менеджменту в умовах кризи)
Keywords: logistics management; compliance program; travel companies; force majeure; systemic crisis; логістичний менеджмент; комплаєнс-програма; туристичні компанії; форс-мажор; системна криза